2023
DOI: 10.1002/glia.24353
|View full text |Cite
|
Sign up to set email alerts
|

The role of glial cells in Zika virus‐induced neurodegeneration

Abstract: Zika virus (ZIKV) is a strongly neurotropic flavivirus whose infection has been associated with microcephaly in neonates. However, clinical and experimental evidence indicate that ZIKV also affects the adult nervous system. In this regard, in vitro and in vivo studies have shown the ability of ZIKV to infect glial cells. In the central nervous system (CNS), glial cells are represented by astrocytes, microglia, and oligodendrocytes. In contrast, the peripheral nervous system (PNS) constitutes a highly heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 122 publications
1
9
0
1
Order By: Relevance
“…In vitro findings have also demonstrated that ZIKV can interfere with all stages of neurogenesis (Vouga and Baud, 2016). The alterations caused by ZIKV in the cells of the nervous system are not restricted only to neurons but can also affect glial cells, as was recently discussed in the literature (Quincozes-Santos et al, 2023).…”
Section: Zika Virusmentioning
confidence: 71%
“…In vitro findings have also demonstrated that ZIKV can interfere with all stages of neurogenesis (Vouga and Baud, 2016). The alterations caused by ZIKV in the cells of the nervous system are not restricted only to neurons but can also affect glial cells, as was recently discussed in the literature (Quincozes-Santos et al, 2023).…”
Section: Zika Virusmentioning
confidence: 71%
“…The attained neurotropic nature of ZIKV makes it capable to infect almost all types of brain cells−microglia, neural progenitor cells and astrocytes; resulting in severe consequences during fetal brain development ( Bhagat et al, 2018 , 2022 ; Quincozes-Santos et al, 2023 ). The associated neurological complications due to vertical transmission (from infected pregnant women to fetus) mainly involves miscarriages, impaired fetal growth or fetuses born with congenital Zika syndrome (CZS) ( van der Linden et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, NRG1 has been shown to be expressed in the early stages of brain development [ 33 ], and it would be interesting to investigate the effect of its repression with respect to ZIKV-induced microcephaly [ 34 ]. In addition, since decreased levels of BDNF have been observed in several neurodegenerative diseases [ 32 ], and ZIKV is potentially associated with the development and/or progression of neurodegenerative diseases [ 35 ], it would be interesting to study the role of BDNF repression in this context. Two other attractive candidates for further studies are the genes DLX5 and ATOH8, which are also repressed in ZIKV-infected cells.…”
Section: Discussionmentioning
confidence: 99%